A glass paste and a method of making the same
By incorporating low-expansion-coefficient fillers and nano-boron nitride into the glass slurry through a mixed ball milling technique, the problem of separation between the glass slurry and the substrate was solved, achieving matching of thermal expansion coefficients and improved adhesion, thereby enhancing the performance of the energy-saving electric heating plate.
Patent Information
- Application Number
- CN202311233607.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-11-21
- Estimated Expiration
- 2043-09-22
AI Technical Summary
The coefficient of thermal expansion of existing glass paste is much greater than that of the substrate glass, causing the coated glass paste to separate from the substrate glass, which affects the performance of the energy-saving electric heating plate.
The filler with a low coefficient of thermal expansion is made by ball milling a mixture of microcrystalline glass powder and nano boron nitride. It is added to the glass powder and mixed evenly with an organic carrier to form a glass slurry, which reduces the coefficient of thermal expansion of the glass slurry and improves its adhesion to the substrate.
It effectively prevents the glass paste from separating from the substrate glass, reduces residual thermal stress caused by deviations in the coefficient of thermal expansion, and improves the adhesion and performance of the glass paste to the substrate.
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of electronic paste, and particularly relates to a glass paste and a preparation method thereof. BACKGROUND
[0002] At present, a microcrystalline glass energy-saving electric heating plate appears in the market. Energy-saving materials are prepared on high-temperature-resistant microcrystalline glass. The "Brown effect" generated in the thermal assembly by the alternating electric field of the energy-saving materials and the mutual impact between carbon atoms and molecular groups convert the electric energy into heat energy in an instant. The heat is dissipated in the form of infrared radiation with a wavelength of 8-14 microns. The effective electric-heat conversion rate is high. The radial current in the electric field of the high-molecular infrared radiation material is extremely small, which ensures safety, fast energy consumption and long service life. The commonly selected energy-saving materials are nano-carbon materials such as graphene, carbon black and carbon nanotubes. However, the nano-carbon materials are generally oxidized at about 500 DEG C in air, which leads to a decrease in power. At present, a protective layer is coated to protect the durability, but the acid, alkali and solvent resistance is poor, which affects the service life. In view of this problem, people use double-sided high-temperature-resistant microcrystalline glass to protect the energy-saving materials in the middle. However, the expansion coefficient of the microcrystalline glass substrate is small (0.1-4.0*10 -6 / ℃), and can even be reduced to 0. If the existing glass paste with an expansion coefficient of 8.0-10.0*10 -6 / ℃ is used, the coated glass paste is easily separated from the substrate glass, which affects the use performance of the energy-saving electric heating plate. Therefore, it is urgent to develop a glass paste with a low expansion coefficient. SUMMARY
[0003] In view of the problem that the expansion coefficient of the existing glass paste is much larger than that of the substrate glass, the coated glass paste is easily separated from the substrate glass, which affects the use performance of the energy-saving electric heating plate, the application provides a glass paste and a preparation method thereof.
[0004] To solve the above technical problems, the application provides a glass paste, which comprises the following components in percentage by mass: 40-60% of glass powder, 10-25% of low-expansion coefficient filler and 25-45% of organic carrier.
[0005] The low-expansion coefficient filler is obtained by mixing microcrystalline glass powder and nano-boron nitride and ball milling.
[0006] Preferably, the mass content of the microcrystalline glass powder is 70-90% and the mass content of the nano-boron nitride is 10-30% based on 100% of the total mass of the low-expansion coefficient filler.
[0007] Preferably, the microcrystalline glass powder comprises the following components in the following mass percentages, based on the total mass of the microcrystalline glass powder being 100%: SiO2: 35% to 45%, Li2O: 5% to 15%, Al2O3: 30% to 40%, TiO2: 1% to 3%, and ZrO2: 1% to 3%.
[0008] Preferably, the low-expansion coefficient filler is obtained by mixing and grinding the microcrystalline glass powder and the nano boron nitride, and specifically comprises the following steps:
[0009] After the following mass percentage components 35% to 45% SiO2, 5% to 15% Li2O, 30% to 40% Al2O3, 1% to 3% TiO2, and 1% to 3% ZrO2 are mixed, heating is performed at a temperature of 1300 to 1500°C for 2 to 6 hours, and then annealing, natural cooling, and heat preservation at 700 to 750°C for 2 to 4 hours are performed to obtain the microcrystalline glass;
[0010] The microcrystalline glass is crushed to obtain the microcrystalline glass powder, and then mixed and ground with the nano boron nitride, and after the grinding is completed, the low-expansion coefficient filler is obtained by passing through a 200-mesh screen.
[0011] Preferably, in the annealing step, the annealing time is 3 to 6 hours.
[0012] In the grinding step, the grinding time is 24 to 50 hours.
[0013] Preferably, the D50 particle size of the nano boron nitride is 500 nm to 3000 nm, and the number of layers of the nano boron nitride is 1 to 10 layers.
[0014] Preferably, the particle size D50 of the glass powder is 1 to 3 microns, the softening temperature is 500 to 550°C, and the glass transition temperature is 450 to 500°C.
[0015] Preferably, the glass powder comprises the following components in the following mass percentages, based on the total mass of the glass powder being 100%: 35% to 55% Bi2O3, 15% to 35% B2O3, 10% to 20% SiO2, 1% to 10% TiO2, 1% to 5% CaO, 1% to 3% BaO, 1% to 3% Al2O3, and 0% to 1.0% ZnO.
[0016] Preferably, the organic carrier comprises the following components in the following mass percentages, based on the total mass of the organic carrier being 100%: 30% to 50% terpineol, 10% to 20% diethylene glycol butyl ether, 20% to 30% diethylene glycol butyl ether acetate, 6% to 10% ethyl cellulose, 1% to 10% dispersant, 1% to 5% thixotropic agent, and 1% to 5% leveling agent.
[0017] Secondly, this application provides a method for preparing the glass slurry described above, comprising the following steps: mixing the organic carrier, the low expansion coefficient filler and the glass powder evenly to obtain a mixture, and grinding the mixture to obtain the glass slurry.
[0018] Beneficial effects:
[0019] Compared with existing technologies, the glass slurry provided in this application has the following advantages: First, adding a low-expansion-coefficient filler to the glass powder further reduces the thermal expansion coefficient of the glass slurry, preventing separation between the coated glass slurry and the substrate glass; simultaneously, the addition of nano-boron nitride avoids residual thermal stress caused by large deviations in the thermal expansion coefficient. Second, compared to directly adding nano-boron nitride to the slurry, this application first mixes and ball-mills nano-boron nitride with microcrystalline glass powder. This mixing method increases the uniformity of the mixture between microcrystalline glass powder and nano-boron nitride, and because the surface of the microcrystalline glass powder has nano-boron nitride, its structure improves the compatibility of boron nitride in the glass slurry system. Third, the elastic modulus of boron nitride is 500–600 GPa, and the thermal expansion coefficient is 2.0 × 10⁻⁶. -6 ~6.5×10 -6 At / ℃, adding nano-boron nitride to the glass slurry can reduce the thermal stress at the interface caused by the difference in thermal expansion coefficients by utilizing the elastic deformation of boron nitride, thereby improving the adhesion between the glass slurry and the substrate. Detailed Implementation
[0020] To make the technical problems solved, the technical solutions, and the beneficial effects of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0021] This application provides a glass slurry comprising the following components by mass percentage: 40%–60% glass powder, 10%–25% low expansion coefficient filler, and 25%–45% organic carrier;
[0022] The low expansion coefficient filler is obtained by ball milling a mixture of microcrystalline glass powder and nano-boron nitride.
[0023] Specifically, the low expansion coefficient filler is obtained by ball milling a mixture of microcrystalline glass powder and nano-boron nitride. This method can improve the uniformity of the mixing of microcrystalline glass powder and nano-boron nitride. At the same time, ball milling allows the nano-boron nitride to be adsorbed onto the microcrystalline glass powder, thereby improving the compatibility of the low expansion coefficient filler in the glass slurry system and helping to improve the uniformity of the mixing of the low expansion coefficient filler and glass powder.
[0024] The glass paste provided by the application has the following effects: firstly, the low-expansion coefficient filler is added to the glass powder, which can further reduce the thermal expansion coefficient of the glass paste, preventing the glass paste after coating from separating from the base material glass; meanwhile, the addition of nano boron nitride also avoids the residual thermal stress caused by the large deviation of the thermal expansion coefficient. Secondly, compared to directly adding nano boron nitride to the paste, the application first mixes and ball-mills the nano boron nitride with the glass-ceramic powder, which, on the one hand, increases the uniformity of the mixing of the glass-ceramic powder and the nano boron nitride, and on the other hand, the surface of the glass-ceramic powder has boron nitride, and the structure improves the compatibility of boron nitride in the glass paste system. Thirdly, the elastic modulus of boron nitride is 500-600 GPa, and the thermal expansion coefficient is 2.0*10 -6 ~ 6.5*10 -6 / ℃ -1 The addition of nano boron nitride in the glass paste can utilize the elastic deformation of boron nitride to weaken the thermal stress generated by the difference in the thermal expansion coefficient of the interface, and improve the adhesion of the glass paste and the base material.
[0025] In the glass paste, the mass content of the glass powder is 40%-60%, such as 40%, 42%, 45%, 48%, 50%, 53%, 55%, 58%, 60%, etc. The mass content of the low-expansion coefficient filler is 10%-25%, such as 10%, 13%, 15%, 18%, 20%, 22%, 24%, 25%, etc. The mass content of the organic carrier is 25%-45%, such as 25%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 45%, etc.
[0026] In some embodiments, the mass content of the glass-ceramic powder is 70-90%, and the mass content of the nano boron nitride is 10-30%, based on the total mass of the low-expansion coefficient filler being 100%.
[0027] In the low-expansion coefficient filler, the mass content of the glass-ceramic powder is 70-90%, and the mass content of the boron nitride is in the range of 10-30%, which is helpful for the adsorption of boron nitride on the surface of the glass-ceramic powder during the mixing and ball-milling process, and improves the compatibility of boron nitride in the glass powder paste system. Specifically, the mass content of the glass-ceramic powder can be 70%, 75%, 80%, 85%, 90%, etc., as long as it is in the range of 70%-90%. The mass content of the boron nitride can be 10%, 15%, 20%, 25%, 30%, etc., as long as it is in the range of 10-30%.
[0028] In the low-expansion coefficient filler, if the content of boron nitride is less than 10%, the content of boron nitride is too low, the thermal expansion coefficient of the glass paste is high, and the adhesion of the glass paste to the substrate is reduced; if the content of boron nitride is higher than 30%, the content of boron nitride is too high, the flowability and density of the paste are poor, the adhesion of the glass paste to the substrate is reduced, and the bonding and sealing performance of the glass paste to the substrate are affected.
[0029] In some embodiments, the microcrystalline glass powder comprises the following components by mass percentage: SiO2: 35% to 45%, Li2O: 5% to 15%, Al2O3: 30% to 40%, TiO2: 1% to 3%, and ZrO2: 1% to 3%.
[0030] The microcrystalline glass powder comprises the above components, and has improved thermal stability, chemical stability, and mechanical strength of the glass paste.
[0031] In some embodiments, the low-expansion coefficient filler is obtained by mixing and grinding the microcrystalline glass powder and nano boron nitride, and specifically comprises the following steps:
[0032] After mixing the following components by mass percentage: 35% to 45% SiO2, 5% to 15% Li2O, 30% to 40% Al2O3, 1% to 3% TiO2, and 1% to 3% ZrO2, heating at a temperature of 1300 to 1500℃ for 2 to 6h, then annealing, natural cooling, annealing at a temperature of 500 to 600℃, and then heat preservation at a temperature of 700 to 750℃ for 2 to 4h, the microcrystalline glass is obtained.
[0033] The microcrystalline glass powder is obtained by crushing the microcrystalline glass, and then mixed and ground with the nano boron nitride. After grinding, the low-expansion coefficient filler is obtained by passing through a 200-mesh sieve.
[0034] Compared with the preparation of glass powder in the prior art, the present application is heated and preserved after cooling to room temperature, mainly to ensure the grain precipitation in the microcrystalline glass, and the uniformity of the particle size is high. The microcrystalline glass powder is crushed and mixed and ground with the nano boron nitride, which can make the microcrystalline glass powder and the nano boron nitride mixed uniformly, and the surface of the nano boron nitride is adsorbed on the microcrystalline glass powder, improving the compatibility of the low-expansion coefficient filler in the glass paste system, and helping to improve the mixing uniformity of the low-expansion coefficient filler and the glass powder.
[0035] In some embodiments, in the annealing step, the annealing time is 2 to 6h.
[0036] In the grinding step, the grinding time is 24 to 50h.
[0037] If the grinding time is too low, the microcrystalline glass powder and the nano boron nitride are not uniformly mixed, which affects the compatibility of the low-expansion coefficient filler in the glass paste system.
[0038] Further preferably, SiO2 with a mass percentage of 35% to 45%, Li2O with a mass percentage of 5% to 15%, Al2O3 with a mass percentage of 30% to 40%, TiO2 with a mass percentage of 1% to 3%, and ZrO2 with a mass percentage of 1% to 3% are mixed, and then are added into a high-temperature furnace and fired at 1450°C for 2.5 hours; then are transferred to a muffle furnace for annealing, the annealing temperature is 550°C, the annealing time is 4 hours, and then are naturally cooled to room temperature. After cooling, the temperature is kept at 700°C to 750°C for 2 hours to obtain the microcrystalline glass. Then the microcrystalline glass is crushed to obtain the microcrystalline glass powder, and then is ball milled together with the nano boron nitride. After ball milling for 50 hours, the low-expansion coefficient filler is obtained by passing through a 200-mesh sieve.
[0039] It can be understood that the present application does not limit the equipment for mixing and firing SiO2, Li2O, Al2O3, TiO2, and ZrO2, and any equipment capable of achieving the heating function is acceptable. Similarly, the equipment used in the annealing step is not limited.
[0040] In some embodiments, the D50 particle size of the nano boron nitride is 500 nm to 3000 nm, and the number of layers of the nano boron nitride is 1 to 10 layers.
[0041] The nano boron nitride has a D50 particle size of 500 nm to 3000 nm. The addition of the nano boron nitride with a D50 particle size of 500 nm to 3000 nm in the glass paste can avoid residual thermal stress caused by a large thermal expansion coefficient difference in the glass paste, and can also utilize the elastic deformation to weaken the stress generated at the interface due to the different thermal expansion coefficients, thereby ensuring the thermal stability of the glass paste. If the D50 particle size of the boron nitride is less than 500 nm, the specific surface area of the boron nitride increases, and the boron nitride is prone to agglomeration due to the small particle size, which affects the uniformity of the mixture of the microcrystalline glass powder and the boron nitride. If the D50 particle size of the boron nitride is greater than 3000 nm, the particle size of the boron nitride is too large, which affects the uniformity of the mixture of the microcrystalline glass powder and the boron nitride, and also reduces the compatibility of the boron nitride in the glass paste system.
[0042] The number of layers of the nano boron nitride is 1 to 10 layers, such as 1 layer, 3 layers, 5 layers, 7 layers, 10 layers, etc.
[0043] In some embodiments, the particle size D50 of the glass powder is 1 μm to 3 μm, the softening temperature is 500 to 550°C, and the glass transition temperature is 450 to 500°C.
[0044] The low-expansion coefficient filler has a microcrystalline glass powder with a thermal expansion coefficient close to 0, and the thermal expansion coefficient of the glass powder deviates greatly from the thermal expansion coefficient of the microcrystalline glass. The nano boron nitride in the low-expansion coefficient filler plays a buffering role, avoiding the residual thermal stress caused by the large deviation of the thermal expansion coefficient. The nano boron nitride cooperates with the microcrystalline glass powder to further reduce the overall thermal expansion coefficient of the glass paste.
[0045] The glass powder further reduces the overall thermal expansion coefficient of the glass paste by being compounded with the low-expansion filler, and realizes the thermal expansion matching of the glass paste and the base glass.
[0046] In some embodiments, the glass powder includes the following mass percentages of components, based on 100% of the total mass of the glass powder: 35%-55% Bi2O3, 15%-35% B2O3, 10%-20% SiO2, 1%-10% TiO2, 1%-5% CaO, 1%-3% BaO, 1%-3% Al2O3, and 0%-1.0% ZnO.
[0047] The preparation of the glass powder includes the following steps: mixing raw materials with a mass percentage of 35%-55% Bi2O3, 15%-35% B2O3, 10%-20% SiO2, 1%-10% TiO2, 1%-5% CaO, 1%-3% BaO, 1%-3% Al2O3, and 0%-1.0% ZnO, uniformly mixing, smelting at a temperature of 1300-1500°C, smelting for 1-3 hours, cooling after smelting, and ball milling after cooling to room temperature to obtain the glass powder. The room temperature is 20±10°C.
[0048] In some embodiments, the organic carrier includes the following components in mass percentages, based on 100% of the total mass of the organic carrier: 30%-50% of terpineol, 10%-20% of diethylene glycol butyl ether, 20%-30% of diethylene glycol butyl ether acetate, 6%-10% of ethyl cellulose, 1%-10% of a dispersant, 1%-5% of a thixotropic agent, and 1%-5% of a leveling agent.
[0049] Specifically, the dispersant is commonly used in the art, such as including at least one of a polyester amide salt and a polyether ester amine salt. The dispersant is used to improve the dispersion performance of the paste, prevent the deposition and aggregation of the glass powder and the low-expansion coefficient filler, and affect the particle size distribution, coating, and use performance of the paste.
[0050] The thixotropic agent is commonly used in the art, such as including at least one of a polyamide wax and castor oil. The thixotropic agent is used to improve the settling performance of the paste, prevent the paste from stratifying and settling during storage, and prolong the service life.
[0051] The leveling agent is commonly used in the art, such as including at least one of silicone, acrylic resin. The leveling agent is used to improve the leveling performance of the paste, prevent the paste from forming concave, convex, pinhole and other defects.
[0052] The terpineol, diethylene glycol butyl ether, diethylene glycol butyl ether acetate in the organic carrier are used as solvents to dissolve the dispersant, thixotropic agent, leveling agent, ethyl cellulose, wet the glass powder, low-expansion filler, adjust the viscosity and solid content of the paste, and improve the flowability of the glass paste. The ethyl cellulose is the main solid-forming component in the organic carrier, provides film-forming property for the glass paste, provides bonding force for the powder particles, gives the paste leveling property, is easily dissolved in the solvent, and is beneficial to the dotting, spraying or coating performance of the paste.
[0053] The preparation of the organic carrier includes the following steps: uniformly mixing 30%-50% terpineol, 10%-20% diethylene glycol butyl ether, 20%-30% diethylene glycol butyl ether acetate, 6%-10% ethyl cellulose, 1%-10% dispersant, 1%-5% thixotropic agent and 1%-5% leveling agent according to the mass percentage, to obtain the organic carrier.
[0054] In the second aspect, the application provides a preparation method of the glass paste, including the following steps: uniformly mixing the organic carrier, the low-expansion filler and the glass powder to obtain a mixture, and grinding the mixture to obtain the glass paste.
[0055] Specifically, the organic carrier, the low-expansion filler and the glass powder are uniformly mixed by using a planetary homogenizer to obtain a mixture; the mixture is ground for 3-5 times by a three-roll grinding device to obtain the glass paste.
[0056] It can be understood that the application does not limit the mixing device used when mixing the organic carrier, the low-expansion filler and the glass powder, and other stirring devices can also be selected as long as they can realize the function of uniformly mixing the three; and the grinding device is not limited either.
[0057] The specific embodiment mode of the application will be further explained and described by the following examples, but the protection scope of the application is not limited in the range described in the examples.
[0058] Example 1
[0059] Preparation of the low-expansion filler:
[0060] The following mass percentage components 45% SiO2, 15% Li2O, 35% Al2O3, 3% TiO2, 2% ZrO2 are mixed, then heated in a high temperature furnace at a temperature of 1450°C for 2.5h, then immediately placed in a muffle furnace for annealing, the annealing temperature is 550°C, the annealing time is 4h, then naturally cooled to room temperature, then heated to 720°C for heat preservation, the heat preservation time is 2h, and the microcrystalline glass is obtained after the heat preservation is completed.
[0061] The microcrystalline glass is crushed, mixed with nano boron nitride with a D50 particle size of 500nm and 1 layer, ball milled for 50h, and sieved through a 200 mesh screen to obtain a low expansion coefficient filler. The mass content of the added microcrystalline glass powder is 90%, and the mass content of the nano boron nitride is 10%.
[0062] Preparation of glass powder:
[0063] The raw materials with mass percentage of 40% Bi2O3, 30% B2O3, 17% SiO2, 7% TiO2, 3% CaO, 1% BaO, 1% Al2O3 and 1.0% ZnO are mixed, and then uniformly mixed and melted at 1500°C for 3h. After the melting is completed, the glass powder is obtained by ball milling after cooling to room temperature.
[0064] Preparation of organic carrier
[0065] According to the mass percentage of 45% of terpineol, 15% of diethylene glycol butyl ether, 30% of diethylene glycol butyl ether acetate, 6% of ethyl cellulose, 1% of dispersant polyester amide salt, 1% of thixotropic agent polyamide wax and 2% of silicone leveling agent, the above components are added into a planetary mixer and uniformly mixed to obtain an organic carrier.
[0066] Preparation of glass paste
[0067] The above prepared organic carrier, glass powder and low expansion coefficient filler are added into a planetary homogenizer and uniformly mixed to obtain a mixture, wherein the mass content of the organic carrier is 25%, the mass content of the low expansion glass powder is 55%, and the mass content of the low expansion coefficient filler is 20%. The mixture is added into a three-roll grinding device and ground for 3 times to obtain a glass paste.
[0068] Example 2
[0069] Example 2 is different from example 1 in that the preparation method of the low expansion coefficient filler is different, and the rest is the same as example 1, which is as follows.
[0070] Preparation of low expansion coefficient filler:
[0071] The preparation method of the microcrystalline glass is the same as that of example 1.
[0072] The microcrystalline glass is crushed and mixed with the nanometer boron nitride having a D50 particle size of 2400 nm and 10 layers to be ball milled for 50 h. After the ball milling, the low-expansion coefficient filler is obtained by passing through a 200-mesh screen. The mass content of the nanometer boron nitride and the microcrystalline glass powder is the same as in Example 1.
[0073] Example 3
[0074] Example 3 differs from Example 1 in that the preparation method of the glass paste is different, and the rest is the same as Example 1, as follows.
[0075] Preparation of the glass paste
[0076] The organic carrier, the glass powder, and the low-expansion coefficient filler prepared above are added to a star homogenizer to be mixed uniformly, to obtain a mixture, wherein the mass content of the organic carrier is 35%, the mass content of the low-expansion glass powder is 45%, and the mass content of the low-expansion coefficient filler is 20%. The mixture is added to a three-roll grinding device to be ground for 5 times, to obtain the glass paste.
[0077] Example 4
[0078] Example 4 differs from Example 1 in that the preparation method of the low-expansion coefficient filler is different, and the rest is the same as Example 1, as follows.
[0079] Preparation of the low-expansion coefficient filler:
[0080] The microcrystalline glass is prepared in the same manner as in Example 1.
[0081] The microcrystalline glass is crushed and mixed with the nanometer boron nitride having a D50 particle size of 2400 nm and 10 layers to be ball milled for 50 h. After the ball milling, the low-expansion coefficient filler is obtained by passing through a 200-mesh screen. The mass content of the nanometer boron nitride and the microcrystalline glass powder is the same as in Example 1.
[0082] Example 5
[0083] Example 5 differs from Example 4 in that the preparation method of the low-expansion coefficient filler is different, and the rest is the same as Example 1, as follows.
[0084] Preparation of the low-expansion coefficient filler:
[0085] The microcrystalline glass powder is prepared in the same manner as in Example 1.
[0086] The microcrystalline glass is crushed and mixed with the nanometer boron nitride having a D50 particle size of 2400 nm and 10 layers to be ball milled for 50 h. After the ball milling, the low-expansion coefficient filler is obtained by passing through a 200-mesh screen. The mass content of the nanometer boron nitride and the microcrystalline glass powder is the same as in Example 1.
[0087] Example 6
[0088] Example 6 differs from Example 1 in that the preparation method of the low-expansion coefficient filler is different, and the rest is the same as Example 1, as follows.
[0089] Preparation of low-expansion coefficient filler:
[0090] The preparation of the glass-ceramic powder is the same as in Example 1;
[0091] The glass-ceramic powder is crushed and mixed with nano-boron nitride with a D50 particle size of 500 nm and 1 layer, and ball milled for 50 h. After ball milling, the low-expansion coefficient filler is obtained by passing through a 200 mesh screen. The mass content of the added glass-ceramic powder is 95%, and the mass content of the nano-boron nitride is 5%.
[0092] Example 7
[0093] Example 7 differs from Example 1 in that the preparation method of the low-expansion coefficient filler is different, and the rest is the same as Example 1, as follows.
[0094] Preparation of low-expansion coefficient filler:
[0095] The preparation of the glass-ceramic powder is the same as in Example 1;
[0096] The glass-ceramic powder is crushed and mixed with nano-boron nitride with a D50 particle size of 500 nm and 1 layer, and ball milled for 50 h. After ball milling, the low-expansion coefficient filler is obtained by passing through a 200 mesh screen. The mass content of the added glass-ceramic powder is 95%, and the mass content of the nano-boron nitride is 5%.
[0097] Comparative Example 1
[0098] Comparative Example 1 differs from Example 1 in that there is no nano-boron nitride in Comparative Example 1. Specifically as follows:
[0099] Preparation of glass-ceramic powder:
[0100] The following mass percentage components 45% SiO2, 15% Li2O, 35% Al2O3, 3% TiO2, 2% ZrO2 are mixed, then heated in a high temperature furnace at a temperature of 1450℃ for 2.5h, then immediately placed in a muffle furnace for annealing, the annealing temperature is 550℃, the annealing time is 4h, then naturally cooled to room temperature, then heated to 715℃-750℃ for insulation, the insulation time is 2h, after insulation, the glass-ceramic is obtained;
[0101] Preparation of glass powder:
[0102] The raw materials with mass percentage of 40% Bi2O3, 30% B2O3, 17% SiO2, 7% TiO2, 3% CaO, 1% BaO, 1% Al2O3 and 1.0% ZnO are mixed, and after being mixed uniformly, they are smelted at 1500°C for 3h, and after the smelting is finished, they are cooled, and after being cooled to room temperature, the glass powder is obtained.
[0103] Preparation of organic carrier
[0104] According to mass percentage: 45% of terpineol, 15% of diethylene glycol butyl ether, 30% of diethylene glycol butyl ether acetate, 6% of ethyl cellulose, 1% of dispersant, 1% of thixotropic agent and 2% of leveling agent. The above components are added into a planetary mixer and mixed uniformly to obtain an organic carrier.
[0105] Preparation of glass paste
[0106] The prepared organic carrier, glass powder and microcrystalline glass powder are added into a planetary homogenizer and mixed uniformly to obtain a mixture, wherein the mass content of the organic carrier is 25%, the mass content of the low-expansion glass powder is 55% and the mass content of the microcrystalline glass powder is 20%. The mixture is added into a three-roll grinding device and ground for 3 times to obtain a glass paste.
[0107] Comparative Example 2
[0108] Comparative Example 2 is different from Example 1 in that nanometer boron nitride is directly added in Comparative Example 2. Specifically as follows:
[0109] Preparation of microcrystalline glass powder:
[0110] The following components with mass percentage of 45% SiO2, 15% Li2O, 35% Al2O3, 3% TiO2 and 2% ZrO2 are mixed, and then heated in a high-temperature furnace at a temperature of 1450°C for 2.5h, and then immediately placed into a muffle furnace for annealing, with an annealing temperature of 550°C and an annealing time of 4h, and then naturally cooled to room temperature, and then heated to 715°C-750°C for holding, with a holding time of 2h, and then the microcrystalline glass powder is obtained after the holding is finished.
[0111] Preparation of glass powder:
[0112] The raw materials with mass percentage of 40% Bi2O3, 30% B2O3, 17% SiO2, 7% TiO2, 3% CaO, 1% BaO, 1% Al2O3 and 1.0% ZnO are mixed, and after being mixed uniformly, they are smelted at 1500°C for 3h, and after the smelting is finished, they are cooled, and after being cooled to room temperature, the glass powder is obtained.
[0113] Preparation of organic carrier
[0114] According to the mass percentage: 45% of terpineol, 15% of diethylene glycol butyl ether, 30% of diethylene glycol butyl ether acetate, 6% of ethyl cellulose, 1% of dispersant, 1% of thixotropic agent and 2% of leveling agent. The above components are added into a planetary mixer and mixed uniformly to obtain an organic carrier.
[0115] Preparation of glass paste
[0116] The above prepared organic carrier, glass powder, glass-ceramic powder and nano boron nitride are added into a planetary homogenizer and mixed uniformly to obtain a mixture, wherein the mass content of the organic carrier is 25%, the mass content of the low-expansion glass powder is 55%, the mass content of the glass-ceramic powder is 18% and the mass content of the nano boron nitride is 2%. The mixture is added into a three-roll grinding device and ground for 3 times to obtain a glass paste. The nano boron nitride has a D50 particle size of 500 nm and 1 layer.
[0117] Comparative Example 3
[0118] Comparative Example 3 is different from Example 1 in that the preparation method of the glass paste is different, and the rest is the same as Example 1, which is as follows.
[0119] Preparation of glass paste
[0120] The above prepared organic carrier, glass powder and low-expansion coefficient filler are added into a planetary homogenizer and mixed uniformly to obtain a mixture, wherein the mass content of the organic carrier is 25%, the mass content of the low-expansion glass powder is 70% and the mass content of the low-expansion coefficient filler is 5%. The mixture is added into a three-roll grinding device and ground for 3 times to obtain a glass paste.
[0121] Comparative Example 4
[0122] Comparative Example 4 is different from Example 1 in that the preparation method of the glass paste is different, and the rest is the same as Example 1, which is as follows.
[0123] Preparation of glass paste
[0124] The above prepared organic carrier, glass powder and low-expansion coefficient filler are added into a planetary homogenizer and mixed uniformly to obtain a mixture, wherein the mass content of the organic carrier is 25%, the mass content of the low-expansion glass powder is 70% and the mass content of the low-expansion coefficient filler is 5%. The mixture is added into a three-roll grinding device and ground for 3 times to obtain a glass paste.
[0125] The glass paste prepared in the above examples 1-7 and comparative examples 1-4 was printed on the glass-ceramic (which had been printed with a heating functional layer) with a wet grinding thickness of 15-30 μm, and then a glass-ceramic substrate was overlaid thereon. The double-layer glass sample was sintered in a muffle furnace at 600°C for 20 min after drying at 150°C for 3-5 min, to obtain a double-layer glass sample. The sample was subjected to cold and hot impact, constant temperature and humidity tests, and the test results are shown in Table 1.
[0126] Cold and hot impact: the double-layer glass sample was tested in the following order: 450°C for 30 min, immediately placed in cold water, 25 cycles, then returned to normal temperature and humidity for 1 h, and then the test sample was measured, and the double-layer glass bonding layer was required to be free of cracking;
[0127] Constant temperature and humidity: the double-layer glass sample was placed in a humidity chamber at 40°C and 88% humidity for 480 h, and then baked in an oven at 60°C for 30 min, and then returned to normal temperature and humidity for 1 h, and then the test sample was measured, and the resistance change rate was required to be less than 10%
[0128] Table 1 Performance data test table of examples 1-7 and comparative examples 1-4
[0129] Group Expansion coefficient (10 -6 / °C) Cold and heat shock Constant temperature and humidity Example 1 3.1 Pass Pass Example 2 3.9 Pass Pass Example 3 3.0 Pass Pass Example 4 3.3 Pass Pass Example 5 3.5 Pass Pass Example 6 4.3 Fail Pass Example 7 4.9 Fail Fail Comparative Example 1 4.3 Fail Pass Comparative Example 2 4.1 Fail Pass Comparative Example 3 4.5 Fail Pass Comparative Example 4 5.1 Fail Fail
[0130] As shown in Table 1, examples 1 and comparative examples 1-2 were compared. In comparative example 1, there was no boron nitride, and the thermal expansion coefficient of the glass paste in comparative example 1 was much higher than that of example 1, and the cold and hot impact test was not qualified. In comparative example 2, nano boron nitride was directly added, and the thermal expansion coefficient was not obviously reduced compared with comparative example 1, and the cold and hot impact test was not qualified. It is shown that in the preparation of the glass paste, the mixing uniformity of the glass-ceramic powder and the nano boron nitride is increased by mixing and ball-milling the nano boron nitride and the glass-ceramic powder. The structure of the glass-ceramic powder with boron nitride improves the compatibility of boron nitride in the glass paste system. The addition of nano boron nitride in the glass paste can utilize the elastic deformation of boron nitride to weaken the thermal stress generated by the different thermal expansion coefficients at the interface, and improve the adhesion of the glass paste and the substrate.
[0131] Examples 1 and comparative examples 3-4 were compared. In comparative example 3, the mass percentage of the low-expansion coefficient filler was less than 10%, and the thermal expansion coefficient of the glass paste was high. In comparative example 4, the mass percentage of the low-expansion coefficient filler was higher than 25%, and the thermal expansion coefficient of the glass paste was high, and the constant temperature and humidity test was not qualified. It is speculated that the excessive amount of the filler leads to poor flowability and density of the paste, increased porosity, and affects the adhesion and sealing performance of the glass paste and the substrate. It is shown that the low-expansion coefficient filler added in the preparation of the glass paste is in the range of 10%-25%, which reduces the thermal expansion coefficient of the glass paste.
[0132] Compared with examples 1, 4-5 and examples 6-7, the content of boron nitride is less than 10%, the thermal expansion coefficient of the glass paste is higher, and the adhesion between the glass paste and the substrate is reduced; the content of boron nitride is higher than 30%, the thermal expansion coefficient of the glass paste is high, the adhesion between the glass paste and the substrate is reduced, and the content of boron nitride is too high, which can cause poor flowability and densification of the glass paste, and affect the adhesion and sealing performance of the glass paste and the substrate; it is indicated that in the low expansion coefficient filler, the content of boron nitride is in the range of 10% to 30%, the thermal expansion coefficient of the glass paste is low, and the adhesion between the glass paste and the substrate is high.
[0133] Compared with examples 1-2, it is indicated that the D50 particle size of nano boron nitride is in the range of 500nm to 3000nm, and the number of layers of nano boron nitride is in the range of 1 to 10, which can avoid the residual thermal stress caused by the large deviation of the thermal expansion coefficient of the glass paste, and also can utilize the elastic deformation to weaken the stress generated by the different thermal expansion coefficients of the interface, and ensure the thermal stability of the glass paste.
[0134] The above only describes the preferred embodiments of the present application, and is not intended to limit the present application, and any modification, equivalent replacement and improvement made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A glass paste, characterized in that, The components, by weight percentage, are as follows: 40%–60% glass powder, 10%–25% low expansion coefficient filler, and 25%–45% organic carrier. The low expansion coefficient filler is obtained by ball milling a mixture of microcrystalline glass powder and nano-boron nitride. Based on the total mass of the low expansion coefficient filler as 100%, the mass content of the microcrystalline glass powder is 70-90%, and the mass content of the nano boron nitride is 10-30%. Based on the total mass of the microcrystalline glass powder as 100%, the microcrystalline glass powder comprises the following components by mass percentage: SiO2: 35%~45%, Li2O: 5%~15%, Al2O3: 30%~40%, TiO2: 1%~3% and ZrO2: 1%~3%.
2. The glass slurry according to claim 1, characterized in that, The low expansion coefficient filler is obtained by mixing and grinding microcrystalline glass powder and nano boron nitride, specifically including the following steps: The following mass percentages were mixed: 35%~45% SiO2, 5%~15% Li2O, 30%~40% Al2O3, 1%~3% TiO2, and 1%~3% ZrO2. The mixture was then heated at 1300~1500℃ for 2~6 hours, followed by annealing and natural cooling at 500℃~600℃. Finally, the mixture was held at 700℃~750℃ for 2~4 hours to obtain microcrystalline glass. The sum of all the above mass percentages equals 100%. The microcrystalline glass is crushed to obtain the microcrystalline glass powder, which is then mixed and ground with the nano boron nitride. After grinding, the powder is passed through a 200-mesh sieve to obtain the low expansion coefficient filler.
3. The glass slurry according to claim 2, characterized in that, In the annealing step, the annealing time is 3~6 hours; In the grinding step, the grinding time is 24~50h.
4. The glass slurry according to claim 1, characterized in that, The D50 particle size of the boron nitride nanoparticles is 500nm~3000nm, and the number of layers of the boron nitride nanoparticles is 1~10 layers.
5. The glass slurry according to claim 1, characterized in that, The glass powder has a particle size D50 of 1μm to 3μm, a softening temperature of 500 to 550℃, and a glass transition temperature of 450 to 500℃.
6. The glass slurry according to claim 1 or 5, characterized in that, Based on the total mass of the glass powder as 100%, the glass powder comprises the following components by mass percentage: 35%~55% Bi2O3, 15%~35% B2O3, 10%~20% SiO2, 1%~10% TiO2, 1%~5% CaO, 1%~3% BaO, 1%~3% Al2O3 and 0%~1.0% ZnO.
7. The glass slurry according to claim 1, characterized in that, Based on the total mass of the organic carrier as 100%, the organic carrier comprises the following components by mass percentage: 30%~50% terpineol, 10%~20% diethylene glycol butyl ether, 20%~30% diethylene glycol butyl ether acetate, 6%~10% ethyl cellulose, 1%~10% dispersant, 1%~5% thixotropic agent and 1%~5% leveling agent.
8. A method for preparing the glass slurry according to any one of claims 1-7, characterized in that, Includes the following steps: The organic carrier, the low expansion coefficient filler and the glass powder are mixed evenly to obtain a mixture, and the mixture is ground to obtain the glass slurry.
Citation Information
Patent Citations
Glass powder, valve plate structure and preparation method
CN111499207A
Resistive paste
US4985176A